An implementation approach for an inter-domain routing protocol for DWDM - Khair, Mazen George (University of Ottawa (Canada), 2004)
Today's Internet applications are in need of additional bandwidth. Consequently, a large number of high capacity fiber optical networks have been deployed. The rapid increase in this need has resulted in more than one optical Autonomous Systems (AS) per geographical area. In order to make optimal use of these widely spread optical networks, an intelligent approach is needed to manage the resources of the networks. In this thesis, we propose a new routing protocol, called Optical Routing Border Gateway Protocol (ORBGP). ORBGP exploits most functionalities of the BGP routing protocol with some modifications to support the exchange of optical routing information. Furthermore, ORBGP introduces two new advertising policies to allow the edge nodes to advertise routing changes based on their needs. The performance of this protocol for different network architectures has been investigated through simulation studies, and the results show promise. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.